Heat transfer and flow characteristics of fluid jets impinging on a surface with cavities - King, Andrew; Chandratilleke, Tilak; Narayanaswamy, Ramesh (Begell House Inc, 2010)
This paper examines the thermal enhancement potential of a novel technique for cooling a heated surface by fluid jet impingement. Instead of using a conventional flat impinging surface, the fluid jet is directed into a coaxial cylindrical cavity embedded in the heated surface. A numerical study is performed to obtain the heat and fluid flow characteristics and to examine the parametric influence arising from the modified surface geometry. Comparisons are made with the thermal performance of conventional fluid jet impingement at a smooth heated surface. The results indicate a several-fold increase in heat transfer due to the presence of a cavity beneath the jet. It is noted that the degree of enhancement is primarily dependent on the cavity depth and jet Reynolds number.